LANGUAGE STYLES OF LARA JEAN COVEY IN ALVAREZ’S FILM TO ALL THE BOYS I’VE LOVED BEFORE - Putri, Novita Melati Ananta; Veniranda, Yohana (UC Journal: ELT, Linguistics and Literature Journal, 2024)
This research aims to investigate the types of language styles used by Lara Jean Covey and the social factors that influence her to use different language styles in Sofia Alvarez’s Film To All the Boys I’ve Loved Before. This research is a content analysis. The source of data was the transcript of the film. Data were analyzed based on the five language styles adopted from Martin Joos’ (1976) and Francis’ (1965) theories. Holmes’ (2001) theory was used to analyze the social factors that influence Lara Jean Covey in using different language styles. The findings showed three types of language styles used by Lara Jean Covey. The three language styles were the consultative style, intimate style, and casual style. The most dominant language style used by Lara Jean Covey in the film is casual style. She tended to use a casual style to make the atmosphere more relaxed. Then, four social factors influencing Lara Jean in using different language styles are participants, setting, topic, and function.